2011
DOI: 10.1017/s0007114511004533
|View full text |Cite
|
Sign up to set email alerts
|

Protein levels in enteral feeds: do these meet requirements in children with severe cerebral palsy?

Abstract: Children with cerebral palsy (CP) have been documented to have feeding difficulties, which increase in line with condition severity and result in lowered growth potential. Much nutrition literature surrounds energy intake and expenditure in these children, with less information available on other parameters such as protein and micronutrients, which are also important for growth and development. We examined differences in protein intake and a variety of protein metabolism indices in children with CP compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 45 publications
1
21
0
2
Order By: Relevance
“…An abnormally low FAD effect may occur in a negative nitrogen balance state, as erythrocytes can take up riboflavin released during tissue breakdown. This would corroborate with findings published elsewhere, documenting potential protein inadequacy in this group of enterally fed children with severe CP 32 …”
Section: Discussionsupporting
confidence: 92%
“…An abnormally low FAD effect may occur in a negative nitrogen balance state, as erythrocytes can take up riboflavin released during tissue breakdown. This would corroborate with findings published elsewhere, documenting potential protein inadequacy in this group of enterally fed children with severe CP 32 …”
Section: Discussionsupporting
confidence: 92%
“…Despite the feeding and swallowing difficulties in a great proportion of the children with CP, different studies showed no differences in protein intake between children with CP and their TD peers . However, to date, it remains unclear whether children with CP have similar protein requirements as TD children.…”
Section: The Pathophysiology Of Sarcopenia: a Multifactorial Concept mentioning
confidence: 99%
“…113 Despite the feeding and swallowing difficulties in a great proportion of the children with CP, different studies showed no differences in protein intake between children with CP and their TD peers. [115][116][117][118] However, to date, it remains unclear whether children with CP have similar protein requirements as TD children. Many people with CP participate in intensive (strengthening) exercise programmes, and because exercise causes muscle micro-damage, it is important to replace and rebuild this tissue to allow for hypertrophy and strength increases.…”
Section: Nutritional Factors: Deficiencies Of Protein and Vitamin Dmentioning
confidence: 99%
“…The majority of these articles (78%) were cohort studies, 5 23,44,53,65,71,74,80,81,83 systematic reviews (5%), 7,49,89,96,97 and controlled trials (5%). 22,28,48,55,91 The 5 systematic reviews performed analyses on 0 to 25 articles each. Years of publication were from 1969 to 2014, and the median total sample size among our included texts was 51 (range, 3-24 920 children).…”
Section: Identifi Cation Of Included Articlesmentioning
confidence: 99%